Stoicism and Fear of Missing Out (Fomo) in The Z Generation’s Trend - Andrean Satriawan; Ris’an Rusli; Rahmat Hidayat (International Journal of Social Service and Research, 2023)
The aim of this study is to talking about a growing phenomenon In this era of massive usage and development of digital media that causes Fear of Missing Out (FoMO) behavior, in this study discusses various aspects of FoMO phenomena, Z generation, and stoicism. FoMO behavior takes place across generations especially the Z generation. The issue in this research is how FoMO affected students of Ushuluddin and Islamic Thought Faculty at UIN Raden Fatah Palembang in their lives. In this case, stoicism play a crucial role in absorbing the rapid negative effects of FoMO behavior cause stoicism is the way of life, in stoicism taught afirm that people are creature that capable to controlling their thoughts, this is the principles of living promoted by stoicism itself. This research focuses on the FoMO phenomena in various trend that happen in Ushuluddin And Islamic Thought Faculty. FoMO stands for Fear of Missing Out which refers to the fear of missing out on enjoyable experiences when someone else is participated in them. The type of the study is a field research. This study has two type of data resources in this research, primary data and secondary data, primary data source is interviews with the students of Ushuluddin And Islamic Thought Faculty, the secondary data is data obtained from graphic documents, internet search, and many other. Apply stoicism in the daily life has a big impact for the student of Ushuluddin And Islamic Thought Faculty cause if they apply stoicism they will not imppacted by FoMO behaviour in the various trends based on stoicism taught that said to reach the true happpines we have to focus on things within our control not the other. The result of this study has shown that those who do not apply the stoicism are particularly susceptible to FoMO behavior, but when someone is able to apply the stoicism, stoicism becomes the cure to avoid FoMO.